Gut microbes in central nervous system development and related disorders - Gan, Yumeng; Chen, Yao; Zhong, Huijie; Liu, Zhuo; Geng, Jiawei; Wang, Huishan; Wang, Wenxue (Frontiers in Immunology, 2024)
The association between gut microbiota and central nervous system (CNS) development has garnered significant research attention in recent years. Evidence suggests bidirectional communication between the CNS and gut microbiota through the brain-gut axis. As a long and complex process, CNS development is highly susceptible to both endogenous and exogenous factors. The gut microbiota impacts the CNS by regulating neurogenesis, myelination, glial cell function, synaptic pruning, and bloodbrain barrier permeability, with implication in various CNS disorders. This review outlines the relationship between gut microbiota and stages of CNS development (prenatal and postnatal), emphasizing the integral role of gut microbes. Furthermore, the review explores the implications of gut microbiota in neurodevelopmental disorders, such as autism spectrum disorder, Rett syndrome, and Angelman syndrome, offering insights into early detection, prompt intervention, and innovative treatments.